Pengembangan Buku Ajar Ekonomi Internasional sebagai Refleksi Perekonomian Global - Prasetyo, Novi Eko; Rakhmadian, Miftah (Universitas Pendidikan Ganesha, 2020)
The focus of developing this international economics textbook is to reflect on the global economy. The assessment of global economic conditions is an achievement of international economic learning. The learning process will be directed at the student's ability to think critically and systematically to achieve learning goals. International economics books have several advantages including 1) This book is in accordance with the economic education study program curriculum, 2) This book is presented contextually so that it can reflect the international economic system in accordance with existing developments. The purpose of this research and development is a reflection of the global economy on national economic conditions. By using the Research and Development (R&D) method, researchers can develop this book according to existing needs. This book has 5 chapters of discussion. The results of the implementation of the application of the international economics book obtained a